Eksplorasi Potensi Ekstrak Etanol Batang Dan Daun Mangrove (Rhizophora Mucronate Poir) Sebagai Antioksidan Alami - Rejeki, Desi Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2022)
Mangroves are common plants found in coastal areas that are affected by the tides of sea water and river estuaries. Most mangrove plants have therapeutic properties. Secondary metabolite chemical compounds found in mangroves include alkaloids, flavonoids, phenols, terpenoids, steroids, and saponins. Antioxidant chemicals are one of the substances produced by mangroves. Antioxidant chemical compounds are available in two types which are synthetic and natural and aim to ward off free radicals. The purpose of this study was to determine the yield of stem and leaf extracts of mangrove plants (Rhizophora mucronate Poir.), and to determine the antioxidant potential value of mangrove plant stem and leaf extracts (Rhizophora mucronate Poir.) by the FRAP method. The results of phytochemical screening tests of mangrove stem and leaf plants contain compounds of Flavonoids, Saponins, Tannins, Terpenoids and Alkaloids. The antioxidant potential in the stem sample was 116.84 mgAAE/gram Extract and the leaves were 126.22 mgAAE/g Extract. The antioxidant yield of mangrove stems and leaves has a strong category.